2020
DOI: 10.1101/2020.06.05.133405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multistage and transmission-blocking targeted antimalarials discovered from the open-source MMV Pandemic Response Box

Abstract: 39New chemical matter is needed to target the divergent biology associated with the different 40 life cycle stages of Plasmodium. Here, we report the parallel screening of the Medicines for 41 Malaria Venture Pandemic Response Box to identify multistage-active and stage-specific 42 compounds against various life cycle stages of Plasmodium parasites (asexual parasites, 43 stage IV/V gametocytes, gametes, oocysts and liver stages) and for endectocidal activity. Hits 44 displayed unique chemotypes and included tw… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…Here, we con rmed the dynamic yet stage-speci c nature of H3K36me2&3 (11) and delineate their roles in the transcriptional reprogramming occurring post-commitment in the gametocyte sexual stage of P. falciparum blood-stage development (34). Our chemical interrogation of P. falciparum HDMs supports these conclusions, highlights the importance of the dynamics of histone methylation for transcriptional control and links aberrant H3K36me2&3 patterns with the increased potency of Jumonji HDM inhibitors towards gametocytes reported before (38,65,66).…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Here, we con rmed the dynamic yet stage-speci c nature of H3K36me2&3 (11) and delineate their roles in the transcriptional reprogramming occurring post-commitment in the gametocyte sexual stage of P. falciparum blood-stage development (34). Our chemical interrogation of P. falciparum HDMs supports these conclusions, highlights the importance of the dynamics of histone methylation for transcriptional control and links aberrant H3K36me2&3 patterns with the increased potency of Jumonji HDM inhibitors towards gametocytes reported before (38,65,66).…”
Section: Discussionsupporting
confidence: 68%
“…JIB-04 (pan-selective) and ML324 (targeting KDM4, PfJMJ3) resulted in the hypermethylation of both H3K36me2&3 relative to the untreated controls (36-to 89-fold, Fig. 5b, Figure S6A), similar to hypermethylation of H3K4me3 and H3K9me3 induced by JIB-04 and ML324 in asexual parasites and gametocytes, respectively (38,66). This hypermethylation was not observed for GSK-J4 (KDM6, H3K27me3 selective, (67) or PCPA-2 (targeting LSD1).…”
Section: Inhibition Of H3k36 Demethylation By Jib-04 Is Associated Wimentioning
confidence: 78%
See 2 more Smart Citations
“…Alternative sources are the de novo screen of natural product libraries in medium-to high-throughput format. It is now clearly indicated that driving screens based on asexual stage potency may not identify transmission-blocking specific compounds and as such we recommend parallel screens against different parasite life cycle stages or at the start, screening driven primarily on the transmissible forms, after which activity against other stages can be determined for hits obtained [131,132]. For such natural product libraries, stringent go/no go criteria need to be defined, similar to screening any other small molecule libraries.…”
Section: Future Perspectivesmentioning
confidence: 99%